Безвізовий режим з ЄС: виклики та перспективи для національної економіки - Дяченко, Тетяна Анатоліївна (ВД "ІНЖЕК", 2019)
Метою статті є з’ясування наслідків впровадження безвізового режиму між Україною та ЄС, виділення їх негативного та позитивного впливу на національну економіку України. З’ясовано, що інтенсифікація процесів євроінтеграції загалом і впровадження безвізового режиму між Україною та ЄС зокрема несе в собі як виклики, так і перспективи для національної економіки України. Проаналізовано основні результати впровадження безвізового режиму для України: кількість поїздок громадян України до ЄС постійно зростає; найпопулярнішим напрямом є Польща; безвізові подорожі сприяють збільшенню експорту з України до ЄС. Досліджено вплив введення безвізового режиму між Україною та ЄС на стан робочої сили в Україні. Проаналізовано стан ринку робочої сили в Україні, виділено його основні негативні тенденції: кількість економічно активного населення в Україні останніми роками постійно убуває; зростає частка безробітного населення; спостерігається демографічна криза та трудова еміграція. Виявлено такі виклики для національної економіки від введення безвізового режиму між Україною та ЄС: зниження трудового потенціалу, падіння обсягу сукупного виробництва, національного доходу, податкових надходжень до держбюджету внаслідок трудової еміграції та «відтоку мізків» до країн – членів ЄС. Обґрунтовано переваги та перспективи для національної економіки від впровадження безвізового режиму, серед яких: зменшення рівня безробіття, зростання рівня заробітної плати й обсягів грошових переказів у результаті трудової еміграції; збільшення експорту з України до ЄС; налагодження міжнародного співробітництва та стимулювання розвитку міжнародної діяльності для національних фірм.

The article is aimed at clarifying the consequences of introduction of the visa-free regime between Ukraine and the EU, allocating their negative and positive impact on the national economy of Ukraine. It is determined that the intensification of processes of the European integration in general and the introduction of the visa-free regime between Ukraine and the EU in particular contains both challenges and prospects for the national economy of Ukraine. The main results of introduction of the visa-free regime for Ukraine are analyzed: the number of trips of Ukrainian citizens to the EU is constantly growing; the most popular destination is Poland; visa-free travels contribute to the increase in exports from Ukraine to the EU. The impact of introduction of the visa-free regime between Ukraine and the EU on the status of labor force in Ukraine is researched. The status of labor market in Ukraine is analyzed, its main negative tendencies are allocated as follows: the number of economically active population in Ukraine has been steadily waning in recent years; proportion of the unemployed population is increasing; a demographic crisis along with labor emigration are observed. The challenges for the national economy from the introduction of visa-free regime between Ukraine and the EU are the following: decrease in labor potential; fall in total production, national income, tax revenues to the State budget as a result of labor emigration and brain drain to the EU Member States. The advantages and prospects for the national economy from introduction of the visa-free regime are substantiated, including the following: reduce in the unemployment rate; rising wages and remittances as result of labor emigration; increased exports from Ukraine to the EU; establishing international cooperation and stimulating international activities for national firms.
Visa-Free Regime with the EU: Challenges and Prospects for the National Economy
Keywords: безвізовий режим; інтеграція; євроінтеграція; трудова міграція; visa-free regime; integration; European integration; labor migration